Endoplasmic Reticulum Protein Quality Control in β Cells. (July 2020) - Shrestha, Neha; Reinert, Rachel B.; Qi, Ling
ABSTRACT: Type 1 and type 2 diabetes are associated with loss of β cell function. Optimal β cell function is linked to protein homeostasis in the endoplasmic reticulum (ER). Here, we review the roles of ER protein quality-control mechanisms, including the unfolded protein response (UPR), autophagy (specifically ER-phagy) and ER-associated degradation (ERAD), in β cells. We propose that different quality control mechanisms may control different aspects of β cell biology (i.e. function, survival, and identity), thereby contributing to disease pathogenesis.